2014
DOI: 10.25100/cm.v45i2.1288
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic liver abscess caused by Gemella morbillorum

Abstract: Even though Gemella morbillorum infection (GMI) is rare in humans, it may, nevertheless, cause endocarditis, meningitis, brain abscess, pleural empyema, nephritis, mediastinitis, and – occasionally – liver abscess. We are describing the case of a 64-year-old Caucasian male admitted with fever and abdominal pain. Laboratory parameters revealed inflammation signs, and instrumental examinations showed the presence of diverticula in the ascending colon. Abdominal ultrasound (US) and computer tomography (CT) showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…G. morbillorum is a facultative anaerobe gram-positive coccus considered to be normal flora of the respiratory, urinary and gastrointestinal tracts in humans 2. Case reports have implicated G. morbillorum as the causative organism of infections throughout the body, most commonly neurological infections and endocarditis 2–6. These tend to occur in immunocompromised hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…G. morbillorum is a facultative anaerobe gram-positive coccus considered to be normal flora of the respiratory, urinary and gastrointestinal tracts in humans 2. Case reports have implicated G. morbillorum as the causative organism of infections throughout the body, most commonly neurological infections and endocarditis 2–6. These tend to occur in immunocompromised hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Gemella morbillorum, formerly known as Streptococcus morbillorum until 1988,1 is part of the normal flora of the respiratory, urinary and gastrointestinal tracts in humans 2. It is an uncommon cause of infection; however, there are case reports in the literature implicating this organism in serious and fatal infections 2–6. Most of these reports are from endocarditis but other organs have also been affected, especially in immunocompromised patients.…”
Section: Introductionmentioning
confidence: 99%
“…Gemella morbillorum , a facultative anaerobic Gram‐positive coccus, is a part of the normal flora of the human oropharynx and gastrointestinal and female genital tracts . Although G. morbillorum is rarely isolated from human infections, it may cause severe localized and generalized infections such as endocarditis , liver abscess , pleural empyema , and brain abscess . Chotai et al reviewed eight previously reported cases of brain abscess caused by G. morbillorum along with their own case; they found that most of the cases (62.5%) were associated with odontogenic infections and previous history of dental procedures.…”
Section: Discussionmentioning
confidence: 99%
“…were reported to cause severe infections. Previously damaged tissue constitutes a risk factor as well [5].…”
Section: Discussionmentioning
confidence: 99%